2007
DOI: 10.1259/dmfr/54883281
|View full text |Cite
|
Sign up to set email alerts
|

Validity of single- and multislice CT for assessment of mandibular condyle lesions

Abstract: All CT-imaging protocols were considered accurate for mandibular condyle lesions assessment. The association of axial with MPR images using multislice CT demonstrated highest accuracy. A new imaging protocol was established for diagnosis of these lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
26
0
5

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 22 publications
1
26
0
5
Order By: Relevance
“…Other studies, however, have claimed that CBCT image quality, regardless of the type of the detector, is comparable or even superior to MDCT. 25 The difference in image display of the 16-row detector CT used in this study compared with the unidetector image display used in the study by Honda et al was examined in another study by Cara et al 4 They investigated the validity of single-and multislice CT for assessments of 15 dry mandibular condyles and found that the highest accuracy was obtained with multislice axial-associated multiplanar reconstructed images. This finding shows that MDCT allows high image quality from thinner slices (0.5 mm) than can be obtained with single-slice CT. 4 This difference can be explained by the fact that the lesions with a depth of less than 1 mm were better detected with thinner slices.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Other studies, however, have claimed that CBCT image quality, regardless of the type of the detector, is comparable or even superior to MDCT. 25 The difference in image display of the 16-row detector CT used in this study compared with the unidetector image display used in the study by Honda et al was examined in another study by Cara et al 4 They investigated the validity of single-and multislice CT for assessments of 15 dry mandibular condyles and found that the highest accuracy was obtained with multislice axial-associated multiplanar reconstructed images. This finding shows that MDCT allows high image quality from thinner slices (0.5 mm) than can be obtained with single-slice CT. 4 This difference can be explained by the fact that the lesions with a depth of less than 1 mm were better detected with thinner slices.…”
Section: Discussionmentioning
confidence: 96%
“…2,3 CT imaging protocols that associate axial with multiplanar reconstructed images in multidetector CT (MDCT) demonstrated the highest accuracy, with 93% sensitivity and 100% specificity. 4 Although the use of CT as a diagnostic tool has been used in medicine for many years, its application in dentistry is limited, mainly because of the high cost of equipment, the large space required for its operation and the high dose of radiation involved. Cone beam CT (CBCT) was introduced as an alternative to CT and is considered appropriate for a wide range of craniofacial indications.…”
Section: Introductionmentioning
confidence: 99%
“…Similar satisfactory results have been observed in the present work. 3,[14][15][16] More recently, cone beam computed tomography has been the object of study for TMJ evaluation by various authors who consider it the best recom- Table 5 -Specificity of the protocols utilized for each region examined by observer 1. Table 6 -Percentages of agreements in relation to the gold standard in the examination of CBCT using the i-CAT Vision Table 4 -Sensitivity of the protocols utilized for each region examined by observer 1.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly to the studies of Utumi et al 20 and Cara et al, 14 the statistical methodology used in this study considered just one intra-observer analysis in order to avoid increasing costs and time, without losing the accuracy of the results, compared to the use of two intra-observer analyses. Additionally, a second observer was not considered because it would not increase sufficiently the number of observers to characterize a statistically representative sample.…”
Section: Discussionmentioning
confidence: 99%
“…[7,12,13] Multiplanar reconstruction (MPR) from MSCT shows the highest accuracy and allows for excellent imaging of discrete bony changes in TMJ arthritis. [14] Typical findings in RA include subjective symptoms, restricted TMJ movement, and radiographic lesions along with condylar erosion, cysts, flattening, and sclerosis. [2] Clinically, a high score in hand-joint space narrowing in RA serves as an early indicator of patients at risk for severe TMD.…”
mentioning
confidence: 99%